Powder and patch ebook - Heyer, Georgette (Historical Romances, 2010)
Georgette Heyer, bestselling author and the Queen of Regency Romance, delights readers with this charming story of a heroine who learns a valuable lesson about being careful what she wishes for. For her, he would do anything... Plainspoken country gentleman Philip Jettan won't bother with a powdered wig, high heels, and fashionable lace cuffs, until he discovers that his lovely neighbor is enamored with a sophisticated man-about-town... But what is it that she really wants? Cleone Charteris sends her suitor Philip away to get some town polish, and he comes back with powder, patches, and all the manners of a seasoned rake. Does Cleone now have exactly the kind of man she's always wanted, or was her insistence on Philip's remarkable transformation a terrible mistake? What readers say: "Georgette Heyer is unbeatable!"—Sunday Telegraph "Charming, charming, charming. And highly readable!" "Witty dialogue and well-developed storylines—even Jane Austen could do no better." "Scintillating and very human love story by an author of exceptional talents." "Ms Heyer's effervescent wit and obvious ability to tell a good and humorous story is already evident, making Powder and Patch an enjoyable and worthwhile read."